2014
DOI: 10.1016/j.jmva.2013.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Application of second generation wavelets to blind spherical deconvolution

Abstract: We adress the problem of spherical deconvolution in a non parametric statistical framework, where both the signal and the operator kernel are subject to error measurements. After a preliminary treatment of the kernel, we apply a thresholding procedure to the signal in a second generation wavelet basis. Under standard assumptions on the kernel, we study the theoritical performance of the resulting algorithm in terms of L p losses (p ≥ 1) on Besov spaces on the sphere. We hereby extend the application of second … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…It would be beyond the scope and size of this article to give a complete survey of such papers here. Examples of other works where wavelets have been used for inverse problems on the sphere are [13,37,40,43]. In [8,23] it was shown that a wavelet-based regularization can be constructed if the svd of the forward operator is known.…”
Section: Introductionmentioning
confidence: 99%
“…It would be beyond the scope and size of this article to give a complete survey of such papers here. Examples of other works where wavelets have been used for inverse problems on the sphere are [13,37,40,43]. In [8,23] it was shown that a wavelet-based regularization can be constructed if the svd of the forward operator is known.…”
Section: Introductionmentioning
confidence: 99%